Green pulp and paper industry : biotechnology for ecofriendly processing - Kumar, Amit (Assistant professor in biotechnology); Pathak, Puneet; Dutt, Dharm (De Gruyter, 2021)
"This book provides recent developments and future perspectives of pulp and paper processing based on biotechnology to replace conventional environmental unfriendly chemical processes. The use of microorganism and microbial enzymes in various processes such as bleaching, deinking, refining, dissolving pulp, debarking & pitch removal, slime control, wastewater treatment and waste material valorisation are discussed."-- Provided by publisher
Keywords: Paper industry -- Environmental aspects.; Wood-pulp industry -- Environmental aspects.; Biotechnology -- Environmental aspects.; Sustainable development.; elektronické knihy; electronic books